Prospecção e caracterização de vírus gigantes em amostras do Rio Negro, Amazônia - Rafael Kroon Campos (2013)
The family Mimiviridae comprises giant DNA viruses that are studied as putative etiological agents of pneumonia in humans. Recent metagenomic studies detected DNA of this virus in natural aquatic ecosystems in some northern countries, as well as a coastal region of Chile. To date, members of the Mimiviridae family were not described in Brazil. While the Brazilian Amazon has a huge biodiversity and there are few studies that adress the virosphere of this biome. This study aimed to explore viruses of the Mimiviridae family and other giant viruses in waters of the Rio Negro, AM, Brazil. Water was collected near Manaus, at various points of the Rio Negro. Water samples were enriched in rice-water medium and filtered (200 nm) to separate the viruses, which are retained on the filter. The samples were then inoculated in amoebae for isolation and amplification of mimivirus DNA from the helicase gene. A new virus of the genus Mimivirus was isolated from the waters of Rio Negro and characterized. This virus was named Samba virus (MBV).Additionally, an associated virophage was also isolated and named Rio Negro virophage (RNV). RNV is the first mimivirus virophage isolated in the Americas.The helicase gene analysis revealed that SMBV was phylogenetically clustered in the mimivirus group A mimivirus, which includes representants as mimivirus and mamavirus. The virophage was identified by real-time PCR using primers for the capsid gene of previously known virophages. Sequence analysis revealed 100%identity of RNV with the virophage Sputnik virus. Biological approach and electronic microscopy identified unique characteristics of SMBV and RNV.This study opens new perspectives for the giant viruses in Brazil.